PROGNOSTIC SIGNIFICANCE OF SERUM FERRITIN LEVELS ON INITIAL DIAGNOSIS IN PATIENTS WITH ACUTE MYELOID LEUKEMIA - Dudok, Dejan; Virijević, Marijana (Srpski medicinski časopis Lekarske komore, 2021)
Introduction/Aim: Acute myeloid leukemia (AML) is a heterogenous malignant disease whose course and outcome are influenced by a number of prognostic factors. Serum ferritin (SF) is often elevated in oncology patients, and it has been shown that it strongly influences an unfavorable outcome in various malignancies. The aim of this study is to assess the effect of high SF values on overall survival and disease-free survival, as well as to assess the correlation of SF values with other prognostic markers, such as clinical and laboratory parameters. Methods: Retrospective analysis included 108 patients diagnosed with AML at the Clinic for Hematology of the Clinical Center of Serbia (CCS), in Belgrade, in the period 2017 - 2019. Patients with acute promyelocytic leukemia, acute mixed lineage leukemia, secondary AML and patients treated with palliative therapy were excluded from the study. Patients were grouped based on the SF cutoff value of 800 μg/L. Results: Patients with higher SF values had a significantly higher incidence of early death (p = 0.020), sepsis in the induction phase of therapy (p < 0.010), and significantly lower initial hemoglobin levels (p = 0.040), as compared to patients with lower SF values. SF at diagnosis appeared to be a significant independent predictive factor of overall survival (p = 0.019) and of disease-free survival (p = 0.040). Conclusion: Our study showed a significant association of high SF values with sepsis in induction, early death, mean hemoglobin, overall survival, and disease-free survival. Identification of SF as an independent prognostic factor and a potential target site of the action of new drugs could contribute to a better prognosis of AML patients.